Detecting the Presence of Methicillin-Resistant Staphylococcus aureus on Acne Extractor used by Some Beauty Salons in Jatinangor - Ng, Jo Sheng; Rukmana, Gita Indah Triyanti; Diana, Inne Arline (Althea Medical Journal, 2017)
Background: Over the past few decades, methicillin-resistant Staphylococcus aureus (MRSA) has become a major cause of nosocomial infection and has recently emerged in the community. Community associated MRSA (CA-MRSA) have grown drastically over the years and have mostly manifested as a form of skin infection. The MRSA infection usually occurs in individuals with skin lesions serving as a site of entry for the bacteria. The aim of this study was to determine if MRSA is presence on the acne extractor used by some beauty salons in Jatinangor.Methods: A total of 40 samples were taken from 14 beauty salons in Jatinangor from September to October 2013. The samples were then cultured on mannitol salt agar. The isolated colonies were then gram stained, followed by catalase and coagulase test. The colonies having positive for Staphylococcus aureus (S. aureus) were then tested for cefoxitin susceptibility.Results: Overall 3 of the isolates were positive for S. aureus and none were positive for MRSA.Conclusions: Only a small fraction of the isolates are positive for S. aureus and no MRSA is detected.. [AMJ.2017;4(1):64â8]DOI:Â 10.15850/amj.v4n1.163Â